The influence of job characteristics on office worker’s job satisfaction / Hazirah Mukhtar - Mukhtar, Hazirah (Faculty of Business and Management, 2018)
Five core job characteristics may influence job satisfaction among office workers. Skill variety, task identity, task significance, autonomy and feedback are among the job characteristics factors that may affect job satisfaction among office workers in SAJ Ranhill Segamat Johor. The primary data has been collected by the researcher through a questionnaire and based on five point Likert scale. The departments involved are Human Resource, Administration, Mechanical and Engineering, Network, Agency and Technical. With 97 respondents, the findings were derived. The survey data from respondents was to analyse using a hierarchical multiple regression analysis. Finding showed that task identity, autonomy and feedback impaired office workers’ job satisfaction. There have two limitations of the study which is cross sectional and generalize are discussed in the light of implications for future research.